Mutational analysis of the virulence region of an Agrobacterium tumefaciens Ti plasmid. - Klee, H J (1983)
Forty-nine Tn3 and Tn5 transposition insertion mutations were introduced into the virulence region of the pTiA6NC plasmid of Agrobacterium tumefaciens. Five Tn5 transposition mutations from an earlier study (D. Garfinkel and E. Nester, J. Bacteriol. 144:732-743, 1980) were also mapped more accurately. These mutations defined five separate loci within the virulence region. Two Tn3 insertions into one of these loci, virA, result in a strain which is only weakly virulent; however, a Tn5 insertion into this locus eliminates virulence. One Tn5 insertion into another locus, virC, results in a strain which is weakly virulent. Two additional Tn5 insertions into this locus eliminate virulence. Insertions into the remaining three loci eliminate virulence entirely.